Mood and behavioural effects of social robots in conversation situations between nursing home residents and caregivers - Shota Okabe; Syuyu Sakane; Ryoko Fukuda; Fumio Harada (Gerontechnology)
Background: Social robots are known to improve mood and communication among older adults in care facilities. Although many studies have focused on robot’s effects on activities involving multiple participants, few have examined their impact in conversational settings, which is crucial for enhancing mood and quality of life. Research aim: This study aims to elucidate the facilitating effects of the social robot ‘aibo’ on the mood and conversation between residents and staff in a care facility, focusing on conversational interactions. Methods: Ten pairs of residents and staff from a care facility participated in a 20-minute conversation in both the presence and absence of aibo (aibo and non-aibo conditions). Residents’ mood changes before and after the conversation were measured using a face scale, while staff mood changes were assessed using both the face scale and the Profile of Mood States Second Edition. The duration of speech, number of turns (turn taking), and degree of conversational depth were analysed using video recordings. Results: A significant increase in positive mood scores was observed for both residents and staff after conversations under the aibo condition. The staff also exhibited a significant reduction in negative emotion scores after the conversation, which was further enhanced by the presence of aibo. The speaking time of the residents did not differ between conditions, but that of the staff decreased significantly under the aibo condition. Furthermore, conversational depth was significantly lower in the aibo condition than in the non-aibo condition. Conclusion: This study demonstrates that, while aibo may not promote conversation itself, its presence can significantly enhance the positive mood effects of conversations. These findings suggest the potential use of social robots, such as aibo, as psychological support tools for residents and staff.